Job Stress among Auditor: Antecedents and Consequences to Dysfunctional Behavior - Ni Wayan Rustiarini (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study aims to prove the effect of task complexity and time budget pressure on auditors' job stress and dysfunctional behavior empirically. This study also examines the job stress role in mediating the relationship between task complexity and time budget pressure on auditors' dysfunctional behavior. This research uses quantitative research methods. The research data collection technique used a survey that is distributed questionnaires to 87 auditors at public accounting firms in Bali. Determination of the sample based on the saturated sampling method. This study uses a PLS-SEM analysis to examine research hypotheses. PLS is considered appropriate in predicting models for theory development. The results reveal that task complexity and time budget pressure are increasing auditor's job stress. However, only time budget pressure has a direct effect on auditors' dysfunctional behavior. The statistical testing results also show that job stress can mediate the relationship between task complexity and dysfunctional behavior. On the other hand, job stress cannot mediate between time budget pressure and dysfunctional behavior.